Proximal myopathy due to discrete carcinomatous metastases in muscle. Issue 4 (April 1983) - Doshi, R; Fowler, T
Abstract : Two patients are described with proximal muscle weakness and electromyographic evidence of a myopathic process. In both, discrete carcinomatous metastatic deposits were found in proximal muscles. The possible clinical implications are discussed.